Performance of Educators in Handling Students' Learning at SDN Kertajaya 4 in The Pandemic Era - Amalia Nurul Azizah; Fitrian Prila Wardani (International Journal of Science and Applied Science: Conference Series, 2021)
The COVID-19 pandemic has had a significant impact on the education sector, especially the teaching and learning process. The purpose of this research is to analyze the performance of educators in handling the learning process of students at SDN Kertajaya 4 during a pandemic. This study uses a qualitative research approach with a case study design. Data were collected through observation, interviews, and documentation.The results of this study indicate that educators have been able to adapt to the situation and utilize various online learning platforms to deliver material to students. However, the lack of adequate facilities and infrastructure as well as challenges in conducting online learning have hampered the performance of educators. To improve educator performance, it is necessary to provide more support and training to use online learning platforms effectively. Overall, this research provides insight into the challenges and opportunities for educators in delivering effective teaching and learning during a pandemic.